USING AUTHENTIC MATERIAL TO IMPROVE THE STUDENTS’ LISTENING SKILL - Yasser Mallapiang (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
The research is aimed to find out the Authentic Materials improve the students’ listening comprehension in terms of inferred meaning comprehension at the Second Year Students’ of SMP Negeri 4 Makassar. This research was an Experimental Research. This research was conducted at SMP Negeri 4 Makassar. The subject of the research is class VIII.And in the academic year of 2014-2015 which consists of 30 students, involved 16 men and 14 women who were taken as the responders of the research. The instrument of this research is listening test namely fill the blank test. The finding of this research shows the mean score of students on pre-test in utterance was 3.13. This was categorized as the poor category and after post-test was 6.3 become fair. The mean score on the pre-test, in conclusion, was 3, 53. This was categorized as very poor and after post-test were 6.8 become fairly good.  The use of authentic materials is one of a good technique in teaching listening Skill. The data indicates that this technique had succeeded to improve the students’ listening skill in terms of inferred meaning comprehension at the Second Year Students’ in SMP Negeri 4 Makassar. Keywords: authentic materials, listening, inferred meaning